Determinación del potencial agrícola del suelo para el cultivo de maíz, papa y frejol a través de datos edafoclimáticos en la parroquia Guaytacama. - Yanza Calva, Jean Pierre (2020)
The objective of the project was to determine the agricultural potential of the soil through edapphoclimatic data, considering variables such as precipitation, temperature, cation exchange capacity, pH, texture, macro and micro nutrient salinity, in order to establish corn, potato and bean crops, by means of a digital model of the Guaytacama parish, using the ArcGIS version 10.2.1 program. In order to obtain soil data and its corresponding determination of nutrients, a physicalchemical analysis of 50 soil samples was performed at the TotalChem Laboratory located in the city of Ambato, randomly placing them at the study site, taking into account the exclusion of urban areas and brocoleras. Similarly, to obtain climatic data, we worked with the WorldClim page, acquiring the average temperature and precipitation from 1970 to 2000....